Research on Vulnerability Assessment Method and Protection Safety Check Method Based on New Power System - Xia, Lin; Yuanlong, Liu; Zhenghao, Wang; Qiang, Li (2024 9th Asia Conference on Power and Electrical Engineering (ACPEE), 2024)
The essence of the concept of defense system is to provide critical and wide area information in real time, quickly evaluate the system vulnerability, and according to the vulnerability analysis of the system, perform timely self-healing, adaptive reconstruction of network structure and power distribution scheme, and provide support for the safe and stable operation of the power grid. Due to the change of the role of new energy, for the new power system, the original passive energy absorption object of the power grid is transformed into an effective support subject that actively participates in the control and adjustment of the power grid and abnormal operation occurs on the system side, and there are obvious differences in the selection of protection strategy and the corresponding system vulnerability evaluation. In this paper, based on the research of the protection strategy and automatic device action strategy of the active distribution network after the access of new energy, the system vulnerability analysis method based on the active distribution network is analyzed. At the same time, for the high vulnerability area, the hierarchical protection coordination strategy based on the three-level coordination principle is given. Through the refined protection action area coordination, the vulnerability level of the area is effectively reduced. At the medium voltage power grid level, due to the global evaluation requirements for the safety of the power grid protection strategy, combined with the idea of system stable classification and safe operation margin, a hierarchical rating system for systematic protection safety based on the integration of regional protection scheme and wide area protection set list is proposed.